1986
DOI: 10.1128/jcm.24.3.357-363.1986
|View full text |Cite
|
Sign up to set email alerts
|

Spheroplastic phase of mycobacteria isolated from patients with Crohn's disease

Abstract: Two strains of an unclassified Mycobacterium species were isolated after 18 and 30 months of incubation of media inoculated with resected intestinal tissues from patients with Crohn's disease. These strains represented the third and fourth isolates of this organism from Crohn's disease patients. Ultrastructural examination of this strain and two previously isolated strains revealed the presence of spheroplasts which eventually transformed into the bacillary form of a previously unrecognized Mycobacterium speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(59 citation statements)
references
References 26 publications
(23 reference statements)
2
53
0
Order By: Relevance
“…Those who support the hypothesis that M. paratuberculosis is responsible for CD reconcile their failures at classic recovery by culture by reporting that they often find small translucent colonies of 0.5 mm size, on the Herrold's egg yolk media, after many months of incubation, which when stained by an acid-fast method contain what are described as coccoid bodies and other amorphous material, pleomorphic forms and rods, or spheroplast-like agents (36)(37)(38)(39)(40). Some of these, one-third it is claimed, when tested by PCR for IS 900 were identified as M. paratuberculosis (41,42).…”
Section: Bacteriologic Culturementioning
confidence: 99%
“…Those who support the hypothesis that M. paratuberculosis is responsible for CD reconcile their failures at classic recovery by culture by reporting that they often find small translucent colonies of 0.5 mm size, on the Herrold's egg yolk media, after many months of incubation, which when stained by an acid-fast method contain what are described as coccoid bodies and other amorphous material, pleomorphic forms and rods, or spheroplast-like agents (36)(37)(38)(39)(40). Some of these, one-third it is claimed, when tested by PCR for IS 900 were identified as M. paratuberculosis (41,42).…”
Section: Bacteriologic Culturementioning
confidence: 99%
“…Consequently, the primary source of infection with Map is an infected animal. There is evidence that Map can exist in vegetative, cell wall deficient (Chiodini et al. 1986), and dormant (Whittington et al.…”
Section: Map– the Organismmentioning
confidence: 99%
“…The three strains, designated Linda, Ben and Dominic, had taken up to 18 months for primary isolation. It was later reported that all three strains had originally been isolated as nonacid‐fast coccobacillary forms that had the ultrastructural appearance of sphaeroplasts (cell wall deficient forms) which, after several months incubation, transformed into characteristic Map ‐like organisms (Chiodini et al. 1986).…”
Section: Evidence Of Map In Crohn's Disease Patientsmentioning
confidence: 99%
“…The spheroplast cultures then reverted to acid-fast Mycobacterium-like organism after a single in vitro passage. 6,7 They were confirmed as MAP culture using IS900 probe. 8 This was followed by several studies, which resulted in mixed results in which MAP or MAP DNA presence ranged from 0 to 100%.…”
mentioning
confidence: 99%